An analysis of the effect of statins on the risk of Non‐Hodgkin's Lymphoma in the Women's Health Initiative cohort. (2nd April 2018) - Desai, Pinkal; Wallace, Robert; Anderson, Matthew L.; Howard, Barbara V.; Ray, Roberta; Wu, Chunyuan; Safford, Monika; Martin, Lisa W.; Schlecht, Nicolas; Liu, Simin; Cirillo, Dominic; Jay, Allison; et al.
Abstract: Statins have been shown to induce a phosphoprotein signature that modifies MYC (myelocytomatosis viral oncogene) activation and to have anti‐inflammatory activity that may impact the risk of Non‐Hodgkin's lymphoma (NHL). We analyzed the relationship between statins and risk of NHL using data from the Women's Health Initiative (WHI). The study population included 161, 563 postmenopausal women ages 50–79 years from which 712 cases of NHL were diagnosed after 10.8 years of follow‐up. Information on statin use and other risk factors was collected by self‐ and interviewer‐administered questionnaires. Multivariable‐adjusted HR and 95% CI evaluating the relationship between statin use at baseline, as well as in a time‐dependent manner and risk of NHL, were computed from Cox proportional hazards analyses. A separate analysis was performed for individual NHL subtypes: diffuse large B‐Cell lymphoma (DLBCL) ( n = 228), follicular lymphoma ( n = 169), and small lymphocytic lymphoma ( n = 74). All statistical tests were two‐sided. There was no significant association between use of statins at baseline and risk of NHL (HR 0.85, 95% C.I. 0.67–1.08). However, in the multivariable‐adjusted time‐dependent models, statin use was associated with a borderline lower risk of NHL (HR 0.81, 95% C.I. 0.66–1.00). Considering subtypes of NHL, statin use was associated with a lower risk of DLBCL (HR 0.62, 95% C.I. 0.42–0.91). This effect was driven by lipophilic statins (HR 0.62, 95% C.I. 0.40–0.96). In the WHI, statins were associated with a lower overall risk of DLBCL, particularly attributable to lipophilic statins. These results may have impact on primary or secondary prevention of NHL, particularly DLBCL. Abstract : We analyzed the association of statin use and risk of non‐Hodgkin's lymphoma in the Women's Health Initiative cohort. Our study is an analysis of 161, 808 women, and 10.8 years of follow‐up; we demonstrated a lower risk of NHL with statin use, particularly in the DLBCL subtype of lymphoma.